Optimizing Nitrogen Sources in Top Dressing for Wheat: Field Study on Growth, Yield, and Ammonia Volatilization - Muhammad Sajid Farooq; Rashid Mahmood; Aaqib Hameed; Sajid Ali; Faisal Nadeem; Tahir Hussain Awan; Ammara Fatima; Zaira Ahmad (Scientifica)
In alkaline calcareous soils, ammonia volatilization is the primary nitrogen (N) loss process, resulting in the reduced N use efficiency of crops. This study aimed at assessing the impact of different N sources for top dressing on ammonia volatilization, as well as their effects on wheat growth and yield over two years. In each year, half of the recommended N was applied as a basal dose using diammonium phosphate (DAP) and urea. The remaining half was top-dressed 35 days after sowing with various sources: prilled urea (PU), granular urea (GU), ammonium sulfate (AS), and calcium ammonium nitrate (CAN) in the first year; PU, urea coated with a urease inhibitor from 20 g (VnU-20) and 40 g (VnU-40) leaves of Vachellia nilotica, biochar-coated urea (BU), and urease inhibitor paraphenylenediamine-coated urea (PPDU) in the second year. Ammonia volatilization losses were tracked for up to 12 weeks from sowing. Ammonia losses from basal-applied N remained consistent in both years, comprising around 4% of the applied N. In the first year, top-dressed AS resulted in the highest losses, followed by GU, while losses from urea and CAN were statistically similar. In the second year, coated fertilizers showed lower ammonia losses compared to PU, with VnU-40 displaying the least losses, 48% less than PU. Nitrogen concentration in wheat grain and straw exhibited a negative correlation with ammonia losses. The choice of top-dressed N source influenced tillering, biological, straw, and grain yields of wheat. In the first year, CAN provided maximum yield benefits, and in the second year, VnU-20 exhibited 27% more grain yield than PU. These findings suggest that top dressing with coated urea, especially VnU-20, has the potential to reduce ammonia losses, improve crop nitrogen status, and enhance economic yield compared to other nitrogen sources.